ID: 107: MITOXANTRONE INHIBITS TGFβ1-INDUCED SIGNALING THROUGH PROMOTING TGFβ RECEPTOR II DEGRADATION. Issue 4 (22nd March 2016) - Jacko, AM; Nan, L; Wei, J; Zhao, J; Zhao, Y
Abstract : Background: The transforming growth factor β1 (TGFβ1) signaling pathway and its downstream effects play a central role in the pathogenesis of pulmonary fibrosis. TGFβ induces the phosphorylation of transcriptional factors SMAD2 and SMAD3, thereby increasing the expression of smooth muscle actin (SMA) and fibronectin (FN), two key proteins in the development of fibrosis. This effect is mediated by two receptors, TGFβ receptor I (TβRI) and TGFβ receptor II (TβRII). The protein stability of TβRI has been well studied, while the molecular regulation of TβRII still remains unclear. This project elucidates the role that Mitoxantrone (MTX), a FDA-approved anti-cancer drug, has in the regulation of TGFβ1 signaling through the reduction of TβRII stability. Methods and Results: To study TGFβ1 signaling, human fetal lung fibroblast cell line (MRC-5) was used. As expected, TGFβ1 treatment of MRC-5 cells induced phosphorylation of SMAD2 and SMAD3, with the ultimate expression of FN and SMA. These effects of TGFβ1 on FN and SMA were attenuated by MTX treatment, without altering SMAD2 and SMAD3 levels. To investigate the molecular mechanisms by which MTX regulates TGFβ1 signaling, we examined the expression of TβRI and TβRII. MTX reduced TβRII levels in time and dose dependent manners, while MTX had no effect on TβRI levels. MTX-induced TβRII degradation was inhibited by proteasome inhibitor (MG-132), not lysosome inhibitor (Leupeptin). Overexpression of HA tagged ubiquitin promoted MTX-induced TβRII degradation, suggesting that TβRII degradation by MTX is through the ubiquitin-proteasome pathway. Further, MTX increased TβRII ubiquitination and reduced TβRII neddylation, which has been known to negatively regulate TβRII stability by c-Cbl. Conclusion: These studies reveal that treatment with MTX reduces the levels of TβRII by increasing its ubiquitination and reduction of TβRII neddylation; therefore, MTX is a potential anti-fibrotic drug for the treatment of pulmonary fibrosis. The study is supported by NIH R01 HL112791 (to YZ), NIH R01GM115389 (to JZ), and American Lung Association Biomedical Research Grant RG350146 (to J.Z.).